ANALISIS PENGARUH HARGA, PERSEPSI KUALITAS, KESADARAN MEREK DAN ASOSIASI MEREK TERHADAP KEPUTUSAN PEMBELIAN TEH BOTOL SOSRO (Studi Pada Mahasiswa S1 Universitas Diponegoro) - Sasky Fitriani, Rafika; Khasanah, Imroatul (Diponegoro Journal of Management, 2015)
In  the  development  of  business  recently  has  created  a window  of  a  high  diversity  of competition with the brand that were offering the same category. Competition affect the decline in brand value and the level of the sales of Teh Botol Sosro.This study aims to to analyze the influence of the price , perception of the quality of , brand awareness and brand association with the resolution of the purchase , case studies the students University Diponegoro an undergraduate degree .The price is considered as a cost attached to get the benefits  .Perception  of  the quality  of  is  an  assessment  of  the quality  of  a  brand  .Brand awareness is the memory and knowledge of a brand .Association is the brand brand konsummen with the memory .Accidental the sampling method used for the sample collection .Data collected from 100 respondents were using the criteria for consideration namely must have once made the purchase of Teh Botol Sosro products .A method of analysis using SPSS 20.0 version of the program .With the results of the analysis shows that the price , perception of quality , brand awareness and brand influential association positive and significant purchase of the decision .With the biggest impact  namely the perception  of the  quality and the influence of the smallest  namely brand association